Sezary syndrome. - Ali, CM; Sikdar, TK; Sultana, N; Hoque, MR; Ahmed, N; Parvez, Z; Kamal, B; Rahman, F (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):497-500 The abstract of this article is available on the PubMed website